How admitting migrants with any skills can help overcome a shortage of workers with particular skills - Oded Stark; Lukasz Byra (University of Tübingen, Faculty of Economics and Social Sciences, 2018)
A country that experiences a shortage of workers with particular skills naturally considers two responses: import skills or produce them. Skill import may result in large-scale migration, which will not be to the liking of the natives. Skill production will require financial incentives, which will not be to the liking of the ministry of finance. In this paper we suggest a third response: impose a substantial migration admission fee, "import" fee-paying workers regardless of their skills, and use the revenue from the fee to subsidize the acquisition of the required skills by the natives. We calculate the minimal fee that will remedy the shortage of workers with particular skills with fewer migrants than under the skill "import" policy.
urn:nbn:de:bsz:21-dspace-844172
Keywords: D62; F22; J24; 330; Skill heterogeneity; Production externalities; Market inefficiency; Shortage of particular skills; Social planner's choice; "Import" of skills; A migration admission fee; Skill acquisition subsidy